Pengembangan Aplikasi Pembayaran Tagihan Listrik berbasis Web (Studi Kasus : Griya Bayar Respon) - Anggtaslih Mutiara Fathony; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
In this era, every company faces fierce competition of fulfilling consumer expectations by providing satisfying services. So it needs to be supported by the use of information technology, to make a profit and be able to compete in a wider market. The Electric Bill Payment Application is a monitoring system for the payment of electricity bills to help administrators, collectors, and Griya Bayar's members. The development of electricity bill payment applications takes a case study at Griya Bayar Respon, Malang Regency. The system development process is carried out using the waterfall method, starting from the needs analysis to testing with an object-oriented approach. In the needs analysis phase, it produces 23 functional needs. The implementation phase utilizes the Laravel framework. System testing that conducted is unit testing with 100% valid data results from 4 functionality tests, integration testing results 100% valid, and validation testing results 100% data valid from 23 functionality of test cases. Non-functional testing is tested using the compatibility and usability parameters. Compatibility was tested using Sortsite software with the result that the electricity bill payment application can run on several browsers including internet explorer (IE), Edge, Firefox, Safari, Opera, Chrome, iOS, and Android. Usability produces an SEQ value of 82.8% that is in the category of excellent and Successful, and the average of SUS is 74 in which means Acceptable.